2022
DOI: 10.1080/15592324.2021.2024733
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of δ‐aminolevulinic acid dehydratase via virus induced gene silencing promotes callose deposition in plant phloem

Abstract: The δ -aminolevulinic acid dehydratase (ALAD) enzyme is an intermediate in the biosynthetic pathway of tetrapyrroles. It combines two δ ‐aminolevulinic acid ( δ ‐ALA) molecules to form the pyrrole, porphobilinogen, an important precursor for plant pigments involved in photosynthesis, respiration, light-sensing, and nutrient uptake. Our recent efforts showed that, in citrus, silencing of ALAD gene via Citrus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It should be noted that the enhanced production of callose and phloem proteins in the susceptible plants is purely a mechanical response: it chokes off the transport of nutrients and other vital molecules and at the same time, does not prevent the spread of CaLas. Killiny et al (2022) suggested that the increased ROS could be one of the factors affecting callose deposition as reported for CaLas-infected citrus trees.…”
Section: Discussionmentioning
confidence: 71%
“…It should be noted that the enhanced production of callose and phloem proteins in the susceptible plants is purely a mechanical response: it chokes off the transport of nutrients and other vital molecules and at the same time, does not prevent the spread of CaLas. Killiny et al (2022) suggested that the increased ROS could be one of the factors affecting callose deposition as reported for CaLas-infected citrus trees.…”
Section: Discussionmentioning
confidence: 71%
“…It does this by combining two molecules of δ-aminolevulinic acid (δ-ALA), which results in the formation of the pyrrole, porphobilinogen. Porphobilinogen is an essential plant pigment precursor engaged in photosynthesis, light-sensing, respiration, and the intake of nutrients [222]. It has been observed that As can impede ALAD [223].…”
Section: Arsenic Stress and The Photosynthetic Systemmentioning
confidence: 99%
“…The advances that were enabled by plant viral vectors were enabled by the ability of such vectors to derive high levels of gene expression in plants over a short period of time without integration, because of the autonomous replication ability and mobility of these vectors in the infected plants [6]. Many plant viruses, such as tobacco rattle virus (TRV); tobacco mosaic virus (TMV); and potato virus X (PVX), have been successfully applied to express foreign proteins in a wide range of plant taxa [6][7][8]. However, these advances are handicapped by limited cargo capacity, which is typically <1 kb, precluding the use of these vectors for the delivery of full-length gene coding sequences and largely limiting their use to virus-induced gene silencing (VIGS) in plants [9].…”
Section: Introductionmentioning
confidence: 99%